The Influence of Social Media, Brand Trust, and Word of Mouth on Parents' Decisions to Choose Muhammadiyah Elementary Schools - Febi Septiyan Ardiansa; Mas Oetarjo (Universitas Muhammadiyah Sidoarjo, 2022)
This study aimed to determine the impact of social media, word of mouth, brand trust on parents and guardians' decision to identify SD Muhammadiyah 2 Tulangan Sidoarjo. This study is a narrative study using quantitative methods. Data collection technique using survey of 100 respondents who are parents and guardians. The analytical technique used in this study was multiple linear regression using SPSS (Social Science Statistical Program) version 22 for windows. The results of this study indicate that the social media variable affects the choice decision, the word of mouth variable affects the choice decision, and the brand trust variable affects the decision to choose SD Muhammadiyah 2 Tulangan Sidoarjo.